DEVELOPING A HUMAN FACTORS CURRICULUM FOR FRONTLINE STAFF TRAINING IN THE NHS - Morgan, L; Pickering, S; New, S; McCulloch, P; Kwon, R; Robertson, E (2013)
The benefits of Human Factors and Ergonomics principles are recognised by the healthcare industry, however the process and the content that is delivered under this premise is not standardised. This paper discusses the development of a training program that aims to address this.